2021
DOI: 10.1038/s41419-021-03744-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the sonic hedgehog pathway activates TGF-β-activated kinase (TAK1) to induce autophagy and suppress apoptosis in thyroid tumor cells

Abstract: The sonic hedgehog (Shh) pathway is highly activated in a variety of malignancies and plays important roles in tumorigenesis, tumor growth, drug resistance, and metastasis. Our recent study showed that the inhibitors of the Shh pathway such as cyclopamine (CP), a Smothened (SMO) inhibitor, and GANT61, a Gli1 inhibitor, have modest inhibitory effects on thyroid tumor cell proliferation and tumor growth. The objective of this study was to determine whether autophagy was induced by inhibition of the Shh pathway a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“… 22 Besides, another recently published study finds that silencing Gli1 induces autophagy by activating transforming growth factor-β-activated kinase 1 (TAK1) and its downstream protein c-Jun N-terminal kinase (JNK) and adenosine monophosphate-activated protein kinase (AMPK). 12 According to these studies, Gli1 might be a potential target for inhibiting the progression of several cancers, including ATC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 22 Besides, another recently published study finds that silencing Gli1 induces autophagy by activating transforming growth factor-β-activated kinase 1 (TAK1) and its downstream protein c-Jun N-terminal kinase (JNK) and adenosine monophosphate-activated protein kinase (AMPK). 12 According to these studies, Gli1 might be a potential target for inhibiting the progression of several cancers, including ATC.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that GANT61 treatment suppressed proliferation but promoted apoptosis in ATC cells. Furthermore, due to the fact that ATC is characterized by a high level of invasion and Gli1 modulates EMT (a critical pathway that regulates invasion in various cancers) in ATC, 12 , 21 , 23 the regulation of GANT61 on invasion and EMT markers was also explored, which revealed that GANT61 repressed invasion and regulated EMT markers in ATC cells. These data highlighted the potential of GANT61 as a treatment option for ATC; however, further in vivo studies should be conducted to verify these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GANT61 has shown the inhibitory effect on the growth of several cancers, including ovarian cancer and neuroblastoma [ 14 , 48 , 49 ]. In thyroid cancer, treatment with GANT61 was shown to induce autophagy and to suppress tumor growth with apoptosis [ 50 , 51 , 52 ]. In addition, it was shown to affect the crosstalk with other signaling pathways, such as PI3K/AKT and TGF-β-activated kinase (TAK1) [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In thyroid cancer, treatment with GANT61 was shown to induce autophagy and to suppress tumor growth with apoptosis [ 50 , 51 , 52 ]. In addition, it was shown to affect the crosstalk with other signaling pathways, such as PI3K/AKT and TGF-β-activated kinase (TAK1) [ 51 , 52 ]. However, the effects of GANT61 for inducing redifferentiation in thyroid cancer are not known.…”
Section: Discussionmentioning
confidence: 99%